Unraveling the genetic architecture of congenital vertebral malformation with reference to the developing spine - Sen Zhao; Hengqiang Zhao; Lina Zhao; Xi Cheng; Zhifa Zheng; Mengfan Wu; Wen Wen; Shengru Wang; Zixiang Zhou; Haibo Xie; Dengfeng Ruan; Qing Li; et al. (Nature Communications, 2024)
Abstract Congenital vertebral malformation, affecting 0.13–0.50 per 1000 live births, has an immense locus heterogeneity and complex genetic architecture. In this study, we analyze exome/genome sequencing data from 873 probands with congenital vertebral malformation and 3794 control individuals. Clinical interpretation identifies Mendelian etiologies in 12.0% of the probands and reveals a muscle-related disease mechanism. Gene-based burden test of ultra-rare variants identifies risk genes with large effect sizes (ITPR2, TBX6, TPO, H6PD, and SEC24B). To further investigate the biological relevance of the genetic association signals, we perform single-nucleus RNAseq on human embryonic spines. The burden test signals are enriched in the notochord at early developmental stages and myoblast/myocytes at late stages, highlighting their critical roles in the developing spine. Our work provides insights into the developmental biology of the human spine and the pathogenesis of spine malformation.